Pemaknaan Pengalaman Bahagia pada Orang Islam - Diana Elfida; Winarini Wilman D. Mansoer; Mirra Noor Milla; Bagus Takwin (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
Two philosophical perspectives on the good life, namely hedonic and eudaimonic, have become references for experts to explain how people understand happiness in Western societies with individualistic culture and the majority of Christians. This descriptive phenomenological study aimed to understand the happiness experiences of a collectivistic Muslim society. The participants in this study were nine Muslims, consists of male and female who were known as religious persons by their relatives. The results of data analysis shows that happiness for a Muslim is a process that provides experiences in overcoming problems and life's trials based on religious guidance. These experiences lead participants to a meaning of happiness as shown by three main themes, namely a sense of being able to overcome problems with acceptance and gratitude, life satisfaction in sufficiency, and a sense of worth for the accomplishment with hard work. The results of this study explain that happiness is a dynamic process that is greatly influenced by persons' understanding and belief in religion.